New data on distribution of the European pond turtle Emys orbicularis (Linnaeus, 1758) in the Podravje region (NE Slovenia) - Marijan Govedič; Milan Vogrin; Dejan Bordjan; Dominik Bombek; Damijan Denac; Tatjana Gregorc; Franc Janžekovič; Nino Kirbiš; Melita Vamberger (Natura Sloveniae)
Ten new observations of the European pond turtle Emys orbicularis (Linnaeus, 1758) in the Podravje region are presented. One observation is fairly old, while the others have been made in the last six years. Most of the data are just random observations and do not give a complete overview of the species distribution in the Podravje region. New data suggest that the European pond turtle is more abundant in the Drava River basin than previously known. Distribution and population size of the species in the Drava River basin still remain to be investigated in detail and not only at the Natura 2000 Drava site, especially in the areas of potential habitats prior to planning any new activities.